Obtención de un bioplástico a partir de cascarilla de café (2024)
With the aim of reducing environmental pollution as a result of inadequate waste management and working towards their use, the aim is to reincorporate a usable solid waste into a new process, therefore the degree project focuses on extraction of cellulose from coffee husks to use it as raw material to obtain a bioplastic, starting with its characterization from a physicochemical point of view and thus select the appropriate parameters that allow the production of the bioplastic and evaluate its mechanical properties. A byproduct that is often discarded in large quantities is the case of coffee husks, which contributes to environmental pollution. The transformation of this waste into a useful and sustainable material is the objective of this project to reduce its impact on the environment.